2009
DOI: 10.1111/j.1471-4159.2008.05860.x
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of m‐calpain increases survival of primary hippocampal neurons following NMDA excitotoxicity

Abstract: The calpain family of cysteine proteases has a well-established causal role in neuronal cell death following acute brain injury. However, the relative contribution of calpain isoforms to the various forms of injury has not been determined as available calpain inhibitors are not isoform-specific. In this study, we evaluated the relative role of m-calpain and l-calpain in a primary hippocampal neuron model of NMDA-mediated excitotoxicity. Baseline mRNA expression for the catalytic subunit of m-calpain (capn2 ) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 58 publications
0
35
0
Order By: Relevance
“…Potentially Protective Effect for ASNA1, Optineurin, and Peripherin in MPP ϩ -induced Cell Death-Previous reports have indicated that calpain activation following neurotoxin challenge is related to various cell death signaling pathways and that many calpain-cleaved substrates play a critical role in maintaining cell survival under physiological conditions (23,28,29). We have also demonstrated that MPP ϩ -mediated cell death is blocked in the presence of calpeptin and overexpressed calbindin-D28K (15,24).…”
Section: Mycin-treated Cells Mppmentioning
confidence: 56%
“…Potentially Protective Effect for ASNA1, Optineurin, and Peripherin in MPP ϩ -induced Cell Death-Previous reports have indicated that calpain activation following neurotoxin challenge is related to various cell death signaling pathways and that many calpain-cleaved substrates play a critical role in maintaining cell survival under physiological conditions (23,28,29). We have also demonstrated that MPP ϩ -mediated cell death is blocked in the presence of calpeptin and overexpressed calbindin-D28K (15,24).…”
Section: Mycin-treated Cells Mppmentioning
confidence: 56%
“…The excitotoxic response resulting from the excessive influx of Ca 2+ through NMDAR channels, with a consequent [Ca 2+ ]i overload, is partly mediated by activation of calpains (Bano et al, 2005;Bevers et al, 2009;Curcio et al, 2015;Roberts-Lewis et al, 1994;Seubert et al, 1989;Wei et al, 2012;Zhou and Baudry, 2006). Calpain activity was indeed shown to contribute to the demise process upon exposure of different types of neurons to toxic concentrations of NMDA (D'Orsi et al, 2012;Jang et al, 2009;Wang and Huang, 2012;Xu et al, 2007;Zhou and Baudry, 2006).…”
Section: Calpain Activation Mediated By Extrasynaptic Nmdarmentioning
confidence: 95%
“…Moreover, calpain inhibition was neuroprotective in in vivo models of excitotoxic injury (Wu et al, 2004), ischemic stroke, and neurodegeneration (Lee et al, 1991;Rami and Krieglstein, 1993;Bartus et al, 1994;Hong et al, 1994). It has also been reported that knockdown of calpain II (mcalpain) increased survival of primary hippocampal neurons after NMDA excitotoxicity (Bevers et al, 2009). Importantly, previous studies did not fully address the question under which cell-death conditions calpain inhibition is neuroprotective and when in the cell death cascade calpains became activated.…”
Section: Discussionmentioning
confidence: 99%